GEOLOGY AND PROSPECT IDENTIFICATION OF BATURAJA INTERVAL, TBLMT BLOCK, SOUTH SUMATRA BASIN - ILMANEL ABDINNI, IRHAM
South Sumatra Basin is one of the basins in West Indonesia which has a great potential of oil and gas resources. TBLMT Block is a part of South Sumatra Basin which has an area of approximately 1.404 km² and has been proven as an oil and gas producer. Structurally, TBLMT Block is located in a syncline zone associated with northwest-southeast trending inverse fault. This research is intended to identify the prospects and to estimate the hydrocarbon resources in TBLMT Block, particularly at the limestone interval of Baturaja Formation. Data used in this research comprise of wireline log of three wells and sidewall core data of three wells, geochemical and biostratigraphy data of Eks-3 Well, checkshot and cutting data of Eks-1 Well, and 2D seismic. Method used in this research consisted of: well data analysis comprise of well to well correlation, petrophysical analysis, cutting and sidewall core analysis; seismic data analysis comprise of well-seismic tie, depth structure map, limestone development, and prospect identification; petroleum system analysis comprise of source rock, reservoir rock, seal rock, overburden rock, trap, migration, and accumulation; Monte Carlo simulation to estimate hydrocarbon resources; risks analysis. Based on the analysis of depth structure map, there are five closures which are classified into hydrocarbon prospects areas. These five prospects are further evaluated by petroleum system analysis, hydrocarbon resources calculations, and risks analysis. Based on the Monte Carlo simulation results, it is known that the total amount of hydrocarbon resources at all prospects without considering the risk factor is 418.38 BSCF assuming gas content, and 301.46 MMSTB assuming oil content. Meanwhile, the total amount of hydrocarbon resources at all prospects with calculating the risk factor is 90.36 BSCF assuming gas content, and 65.107 MMSTB assuming oil content. The results of the prospect ranking in the research area, from highest to lowest are: prospect 5, prospect 1, prospect 3, prospect 2, and prospect 4.